Targeted Subsidies and Private Market Participation: An Assessment of Fertilizer Demand in Nigeria - Liverpool-Tasie, Lenis Saweda O. (International Food Policy Research Institute, 2012)
Though input vouchers are being publicized as a mechanism to simultaneously target subsidies and develop demand in private markets, limited empirical evidence of their effect on private input demand exists. Few empirical studies, if any, exist on the effect of targeted subsidies on private input demand in Nigeria or West Africa . Consequently this study begins to fill this gap by estimating the effect of a targeted input subsidy on farmer participation in the private fertilizer market in Nigeria. Using a double hurdle model and a control function approach, this study explores the effect of increasing access to subsidized fertilizer on farmer participation in the private fertilizer market in Kano, Nigeria. The study finds evidence that farmers who received subsidized fertilizer in 2009 tended to have less assets than their counterparts who did not. Within this context, although receiving subsidized fertilizer did not appear to increase the probability of participating in the private fertilizer market, it did increase the quantity of fertilizer purchased from the private market once the decision to participate had been made. It appears that one benefit of the voucher program was that it developed links between rural farmers and input suppliers. Furthermore, where private fertilizer markets are weak, results indicate that there could be significant gains from the temporary use of voucher programs to create links between input suppliers and farmers.